2015
DOI: 10.1021/acs.jpclett.5b00957
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Crowding Arising from Small Molecules, Molecular Constraints, Surface Packing, and Nano-Confinement

Abstract: The effect of macromolecular crowding on the structure, dynamics, and reactivity of biomolecules is well-established and the relevant research has been extensively reviewed. Herein, we focus our discussion on crowding effects arising from small co-solvent molecules and densely packed surface conditions. In addition, we highlight recent efforts that capitalize on the excluded volume effect for various tailored biochemical and biophysical applications. Specifically, we discuss how a targeted increase in local ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 82 publications
1
25
0
Order By: Relevance
“…The reason that we chose this particular system as the testbed is based on the following considerations: (1) our results indicated, as discussed above (Figure 3), that under this condition the solute experiences a DMSO-like environment, indicating preferential accumulation of DMSO molecules near the indole ring; (2) a previous simulation study by Bagchi and coworkers 26 on Trp solvated by DMSO-water mixtures indicated that when the fraction of DMSO is larger than 15%, preferential interactions between the indole ring and DMSO occur wherein the solvent molecules form a distinct network or cluster surrounding the solute enhanced by favorable solvent-solute hydrophobic interactions; (3) we hypothesized that such a scenario also happens in DMSO-TFE mixtures, which can be tested by measuring the spectral diffusion dynamics 28 of the C≡N stretching vibrations via 2D IR spectroscopy as cluster formation has been shown to result in a prolonged spectral diffusion time. 29,30 As shown (Figure 8), 2D IR spectra of the C≡N band of 3M5CI obtained at 4 different waiting times ( T ) clearly indicate spectral diffusion dynamics, as manifested by changes in the contour of the 2D peak corresponding to the 0–1 transition. However, even at the longest waiting time of the experiment, 20 ps, this 2D peak still shows an appreciable tilt towards the diagonal direction, signifying the slowness of the spectral diffusion process.…”
Section: Resultsmentioning
confidence: 71%
“…The reason that we chose this particular system as the testbed is based on the following considerations: (1) our results indicated, as discussed above (Figure 3), that under this condition the solute experiences a DMSO-like environment, indicating preferential accumulation of DMSO molecules near the indole ring; (2) a previous simulation study by Bagchi and coworkers 26 on Trp solvated by DMSO-water mixtures indicated that when the fraction of DMSO is larger than 15%, preferential interactions between the indole ring and DMSO occur wherein the solvent molecules form a distinct network or cluster surrounding the solute enhanced by favorable solvent-solute hydrophobic interactions; (3) we hypothesized that such a scenario also happens in DMSO-TFE mixtures, which can be tested by measuring the spectral diffusion dynamics 28 of the C≡N stretching vibrations via 2D IR spectroscopy as cluster formation has been shown to result in a prolonged spectral diffusion time. 29,30 As shown (Figure 8), 2D IR spectra of the C≡N band of 3M5CI obtained at 4 different waiting times ( T ) clearly indicate spectral diffusion dynamics, as manifested by changes in the contour of the 2D peak corresponding to the 0–1 transition. However, even at the longest waiting time of the experiment, 20 ps, this 2D peak still shows an appreciable tilt towards the diagonal direction, signifying the slowness of the spectral diffusion process.…”
Section: Resultsmentioning
confidence: 71%
“…However, for a peptide with many different side chains, although simultaneous interactions with multiple TPA + clusters are still feasible, there is no guarantee that these clusters are adjacent to each other, thus reducing the possibility of forming a continuous membrane-like environment across the entire peptide and hence α-helix formation. Finally, it is worth noting that unlike clusters formed by protein-protecting cosolvents (46) that are excluded from the protein surface, the excluded-volume or crowding effect of TPA + clusters is more localized and, as a result, will not increase the protein stability through this entropic cause.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the dimensions of a system may impact molecular interactions. Vast differences in spatial confinement exist within cells – from the cytoplasm and intracellular organelles, to vesicles, synapses, and cristae – making it essential to investigate how spatial confinement alters molecular behavior across scales .…”
Section: Introductionmentioning
confidence: 99%